2023
DOI: 10.1108/cr-07-2022-0102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bank competition on financial stability-a study on Indian banks

Abstract: Purpose Nowadays, the competition is not only emerging from within the banking sector, but nonbanking companies like nonbanking financial companies (NBFCs) and FinTech are also growing in size and numbers, offering innovative financial products and services, giving a stiff competition to Indian banks. Thus, this study aims to investigate whether competition from within and outside the banking sector enhances or reduces the financial stability of the banking industry. Design/methodology/approach The study use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…According to Malaysian data, financial stability is positively affected regardless of bank size, type (Islamic or conventional) or management style. A study of the stability of the Indian financial system (Verma and Chakarwarty, 2023) confirmed that financial innovation has a positive and significant impact on financial stability, but the development of fintech is closely related to the growth of cybercrime, which undermines the stability of the banking sector. Liem et al (2022) studied the impact of credit-information sharing on banking stability using data from 73 countries.…”
Section: Financial Stability and Sustainable Growthmentioning
confidence: 99%
“…According to Malaysian data, financial stability is positively affected regardless of bank size, type (Islamic or conventional) or management style. A study of the stability of the Indian financial system (Verma and Chakarwarty, 2023) confirmed that financial innovation has a positive and significant impact on financial stability, but the development of fintech is closely related to the growth of cybercrime, which undermines the stability of the banking sector. Liem et al (2022) studied the impact of credit-information sharing on banking stability using data from 73 countries.…”
Section: Financial Stability and Sustainable Growthmentioning
confidence: 99%
“…Artificial intelligence has empowered the industry, enhancing predictive intelligence, process efficiency, cost optimization, and client engagement (Ashish Kumar, 2022). Competition in the financial sector has evolved, with non-banking companies and Fintech firms offering innovative financial products and services (Divya Verma, 2023). This competition has led to an increase in Fintech startups in India, focusing on digital innovations and technology-enabled business models.…”
Section: Objectivesmentioning
confidence: 99%
“…The sector has witnessed the emergence of new business models like FinTech 2.0 and FinTech 3.0, which concentrate on providing financial inclusion to MSMEs through fintech. [6][7][8] The industry has witnessed the adoption of innovative financing solutions, such as equipment leasing and rental. Additionally, new financing options like FinTech and LeaseTech have also emerged.…”
Section: Performance Dynamics Of Indian Fintech Startupsmentioning
confidence: 99%
“…Post the GFC of 2008, various studies highlighted the detrimental effect of shadow banking on the financial stability of economies due to their asset–liability mismatches and lack of explicit government guarantees (Adrian & Ashcraft, 2012; Bengtsson, 2013). Empirical evidence shows them to be dependent on short-term funding and highly interconnected with OFIs (Anshuman & Sharma, 2020; Chaturvedi & Singh, 2022; Verma & Chakarwarty, 2023).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%